2011
DOI: 10.1016/j.kjms.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its correlates among heroin users in Taiwan

Abstract: The aims of this study were to compare the quality of life (QOL) between subjects with and without heroin use and to examine the association of QOL with sociodemographic characteristics, characteristics of heroin use, family support, and depression among heroin users at entry to a methadone maintenance treatment program. A group of 123 heroin users who visited an outpatient addiction treatment clinic in southern Taiwan for methadone maintenance treatment were recruited into this study. We also recruited 106 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 48 publications
(50 reference statements)
7
31
1
3
Order By: Relevance
“…Domain scores are scaled in a positive direction, scaled from 0 to 100, with higher scores indicating a higher quality of life. Validity and reliability of WHOQOL-BREF have been verified [28], and previous studies assessing the heroin users’ quality of life have applied WHOQOL-BREF [29]. The Chinese version of the instrument used in the present study also showed good validity and reliability [30], and the normal values of the Chinese population by WHOQOL-BREF is as follows [30]: physical domain: 69.38 ± 10.57, psychological domain: 61.81 ± 8.41, social domain: 62.06 ± 9.18, and environmental domain: 60.63 ± 8.70.…”
Section: Methodsmentioning
confidence: 99%
“…Domain scores are scaled in a positive direction, scaled from 0 to 100, with higher scores indicating a higher quality of life. Validity and reliability of WHOQOL-BREF have been verified [28], and previous studies assessing the heroin users’ quality of life have applied WHOQOL-BREF [29]. The Chinese version of the instrument used in the present study also showed good validity and reliability [30], and the normal values of the Chinese population by WHOQOL-BREF is as follows [30]: physical domain: 69.38 ± 10.57, psychological domain: 61.81 ± 8.41, social domain: 62.06 ± 9.18, and environmental domain: 60.63 ± 8.70.…”
Section: Methodsmentioning
confidence: 99%
“…Према дефиницији Светске Здравствене Организације (WHO) квалитет живота пред-ставља болесникову оцену сопственог поло-жаја у животу у контексту културе и система вредности у којима живи, као и према својим циљевима, очекивањима, стандардима и инте-ресовањима 7 . Студије су показале да опиои-дни зависници имају лошији квалитет живота у односу на општу популацију [8][9][10] . Хероински корисници имају лошији квалитет живота у физичким, психолошким и социјалним доме-нима од не-корисника.…”
unclassified
“…Хероински корисници имају лошији квалитет живота у физичким, психолошким и социјалним доме-нима од не-корисника. На квалитет живота ових особа у великој мери утичу коморбиди-тет (као што је депресија) и слаба породична подршка 10 . Терапија метадонским одржавањем је показала позитиван и статистички значајан ефекат на квалитет живота пацијената 1,[11][12][13] .…”
unclassified
“…Impacts of MMT programs in Asia have been evaluated in longitudinal studies (Musa, Abu Bakar, & Ali Khan, 2012;Tran et al, 2012e, 2012g;Wang et al, 2012;Xing et al, 2012;Yen, Wang, Wang, Chen, & Chang, 2011). The primary measures of health outcomes basically included changes in drug use behaviours and health-related quality of life (HRQOL).…”
Section: Discussionmentioning
confidence: 99%